Do Lidocaine Patches Reduce Opioid Use in Acute Rib Fractures?. Issue 9 (September 2020) - Johnson, Matthew; Strait, Lauren; Ata, Ashar; Bartscherer, Ashley; Miller, Claire; Chang, Andrew; Stain, Steven C.; Tafen, Marcel
Background: Pain control is an important aspect of rib fracture management. With a rise in multimodal care approaches, we hypothesized that transdermal lidocaine patches reduce opioid utilization in hospitalized patients with acute rib fractures not requiring continuous opioid infusion. Methods: We performed a retrospective analysis of adult trauma patients with acute rib fractures admitted to the Trauma Service from January 2011 to October 2018. We compared patients who received transdermal lidocaine patches to those who did not and evaluated cumulative opioid consumption, expressed in morphine milligram equivalents (MMEs). Secondary outcomes included the rate of pulmonary complications and length of hospital stay. Results: Of the 21 190 trauma admissions, 3927 (18.5%) had rib fractures. Overall, 1555 patients who received continuous opioid infusion were excluded. Of the remaining 2372 patients, 725 (30.6%) patients received lidocaine patches. The mean total MME of patients who received lidocaine patches was 55.7 MME (30.7 MME on multivariate analysis) and was lower than that of patients who did not receive lidocaine patches ( P ≤ .01). There was no difference in hospital length of stay (no lidocaine patches vs received lidocaine patches: 6.2 days vs 6.5 days, P = .34) or pulmonary complications (1.7% vs 2.8%, P = .08). Discussion: In admitted trauma patients with acute rib fractures not requiring continuous intravenous opiates, lidocaine patch use was associated with a significant decrease in opiate utilization during the patients' hospital course.